Temperature Control System for Heating-Holding Heater Based Arduino With Monitoring Via Webserver - Golfrid Gultom; Abdul Azis Rahmansyah; Dejoi Situngkir; Manan Ginting (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2021)
Heat and hold method is a method with temperature containment techniques in accordance with desired temperature and time functions. This technique aims in adjusting the characteristics of microbial resistance to temperature and saving energy consumption. In this study, a tank with temperature control system was designed for heat and hold the temperature according to the system requirements. Control of the temperature in the heating tank can be done based on the Arduino microcontroller. Arduino reads data from the temperature sensor and activate the heater according to temperature set on the Arduino. Arduino Ethernet Shield acts as Arduino data communication with a database connected to the internet network. The results of this study are in the form of a prototype that shows an IoT-based temperature monitoring tool that can be accessed anywhere via Web-based monitoring system interface. The test was carried out in 2 stages, namely testing by determining target of heater and testing with Holding and Heating with a delay of 10 minutes and 20 minutes. The heating tank temperature control system maintain a temperature of 40oC, 50oC, 60oC for 10 minutes. The temperature holding condition at a certain time is called holding. Henceforth the system temperature is at 70oC.